Advantages and disadvantages of negative pressure wound therapy in equine wound treatment - Anastasiya A. Skvortsova; Ekaterina A. Pavlovskaya; Vladimir N. Obolenskiy (RUDN Journal of Agronomy and Animal Industries, 2025)
The method of wound surface preparation for application of local negative pressure (LNP) is described in detail. The features of dressing attachment depending on the anatomical localization of the wound are presented. The duration of wound healing in the experimental and control (with application of antiseptic and antibacterial preparations) groups, as well as the results of cytomorphological and bacterial studies are given. The most favorable phase of the wound process for application of the LNP method is revealed. Acceleration of granulation tissue formation and epithelialization of the wound surface is observed. The average rate of wound healing with LNP was 3040% higher compared to treatment with antiseptic and antibacterial preparations. The advantages and disadvantages of LNP application in clinical practice are revealed.